Spread of segmental/multifocal idiopathic adult-onset dystonia to a third body site. (June 2021) - Ercoli, Tommaso; Erro, Roberto; Fabbrini, Giovanni; Pellicciari, Roberta; Girlanda, Paolo; Terranova, Carmen; Avanzino, Laura; Di Biasio, Francesca; Barone, Paolo; Esposito, Marcello; De Joanna, Gabriella; Eleopra, Roberto; et al.
Abstract: Background: Adult-onset focal dystonia can spread to involve one, or less frequently, two additional body regions. Spread of focal dystonia to a third body site is not fully characterized. Materials and methods: We retrospectively analyzed data from the Italian Dystonia Registry, enrolling patients with segmental/multifocal dystonia involving at least two parts of the body or more. Survival analysis estimated the relationship between dystonia features and spread to a third body part. Results: We identified 340 patients with segmental/multifocal dystonia involving at least two body parts. Spread of dystonia to a third body site occurred in 42/241 patients (17.4%) with focal onset and 10/99 patients (10.1%) with segmental/multifocal dystonia at onset. The former had a greater tendency to spread than patients with segmental/multifocal dystonia at onset. Gender, years of schooling, comorbidity, family history of dystonia/tremor, age at dystonia onset, and disease duration could not predict spread to a third body site. Among patients with focal onset in different body parts (cranial, cervical, and upper limb regions), there was no association between site of focal dystonia onset and risk of spread to a third body site. Discussion and conclusion: Spread to a third body site occurs in a relative low percentage of patients with idiopathic adult-onset dystonia affecting two body parts. Regardless of the site of dystonia onset and of other demographic/clinical variables, focal onset seems to confer a greater risk of spread to a third body site in comparison to patients with segmental/multifocal dystonia at onset. Highlights: Spread to a third body site occurred in a relative low percentage of patients. Patients with focal dystonia onset had a greater tendency to spread. The site of dystonia onset did not affect the spread to a third body site. None of the demographic/clinical features affected the risk of spread.